2007
DOI: 10.1111/j.1365-2036.2007.03405.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical needs of patients with chronic gastrointestinal symptoms after pelvic radiotherapy

Abstract: SUMMARY BackgroundAfter radiotherapy for pelvic cancer, gastrointestinal symptoms affecting quality of life are common. How they affect daily living is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
1
28
0
Order By: Relevance
“…A cross sectional study of 989 prostate cancer patients treated with RT showed that defecation urgency was the most common symptom among survivors after 2-14 years' follow-up, followed by faecal leakage and loose stools (16). Similar results have been presented in patients treated with pelvic irradiation, both men and women, where defecation urgency and faecal leakage has been identified as the most disturbing of all radiation-induced symptoms (17)(18)(19)(20)(21). In the neoadjuvant study (12), differences between the groups at the three months' assessment, before the start of RT, were found for 'overall quality of life', 'fatigue' and 'sexual interest', all in favour of monotherapy.…”
Section: Discussionsupporting
confidence: 68%
“…A cross sectional study of 989 prostate cancer patients treated with RT showed that defecation urgency was the most common symptom among survivors after 2-14 years' follow-up, followed by faecal leakage and loose stools (16). Similar results have been presented in patients treated with pelvic irradiation, both men and women, where defecation urgency and faecal leakage has been identified as the most disturbing of all radiation-induced symptoms (17)(18)(19)(20)(21). In the neoadjuvant study (12), differences between the groups at the three months' assessment, before the start of RT, were found for 'overall quality of life', 'fatigue' and 'sexual interest', all in favour of monotherapy.…”
Section: Discussionsupporting
confidence: 68%
“…Although this tool is not in common use among oncologist or radiographers, we have previously shown that it is more sensitive than commonly used scoring systems in characterizing symptoms associated with both phases (11,12). It incorporates questions that others have found are important but lacking in more commonly used tools (frequency, urgency, and diarrhea) (13) and symptoms that we have found important to patients (anorectal symptoms and excessive flatus) (14), which are ignored by most scoring tools. Our findings support those that have suggested a predictive association between the occurrence of acute and late effects, with those experiencing moderate to severe acute effects being at least twice as likely to experience late effects (1,3,7,9).…”
Section: Discussionmentioning
confidence: 92%
“…To our knowledge this specific symptom has not been reported previously. However, others have brought to attention the bother caused by excess flatulence [3,4,16]. In a study from the Norwegian Radium Hospital, 53/154 (38%) men were bothered by moderate to severe flatulence after radiation therapy for prostate cancer [15].…”
Section: Discussionmentioning
confidence: 98%
“…Patients treated with pelvic irradiation, both men and women, identify defecation urgency and fecal leakage as the most problematic of all radiation-induced gastrointestinal symptoms [4,15]. Several authors report defecation urgency as one of the most commonly occurring and persisting symptoms after pelvic irradiation [16][17].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation